An Econometric Analysis of Agricultural Production and Economic Growth in India - Kulshrestha, Dhiresh; Agrawal, Kiran Kumar (Indian Journal of Marketing, 2019)
Agriculture continues to be the backbone of the Indian economy-this is hardly an extravagant statement. India is the world’s second most populous country after China. India is the world’s largest producer of jute, pulses, and milk and ranks as the second largest producer of wheat, rice, cotton, groundnut, sugarcane, and horticulture crops. In the present study, the interrelationships between agricultural production and economic growth were studied in an interdependent framework for economic growth keeping in view set policy guidelines for agricultural development in India. The econometric model is formulated with aggregate information available over the period of 1961-2017 (economic reforms to new India concept) and both static and Augmented Dickey-Fuller test (ADF) along with Johansen co-integration test and regression analysis were carried out to assess the performance of the set model. This study examined the agricultural production and its impact on economic growth in India. The study revealed that if there had been no increase in agricultural output (explanatory variables) in India, it would have negatively impacted the economic growth in India.